Historical understanding and ethics in social science - Tsilipakos, Leonidas (Routledge, 2025)
"Can social scientific description capture the historically individual? Is the idea of an ethically committed social science morally defensible? This book offers a critical, historically-grounded perspective on these perennial methodological and ethical problems, in their current forms. It provides a series of in-depth examinations of recent work by prominent authors in sociology and philosophy. The book draws on the thought of Peter Winch to provide a coherent response to the core issues that underlie past and present debate in social science and to provide a solid basis for future inquiry. The book will be of particular interest to social scientists, philosophers, and historians, and to anyone seeking a clear grasp of the demands made by historical understanding and ethics on the study of society"-- Provided by publisher.
Keywords: Social sciences -- History.; Social sciences -- Moral and ethical aspects.; elektronické knihy; electronic books